Big3. Editorial - Lehmann, Christoph U.; Séroussi, Brigitte; Jaulent, Marie-Christine (Yearbook of Medical Informatics, 2014)
Objectives: To provide an editorial introduction into the 2014 IMIA Yearbook of Medical Informatics with an overview of the content, the new publishing scheme, and upcoming 25th anniversary.Methods: A brief overview of the 2014 special topic, Big Data -Smart Health Strategies, and an outline of the novel publishing model is provided in conjunction with a call for proposals to celebrate the 25th anniversary of the Yearbook.Results: ‘Big Data’ has become the latest buzzword in informatics and promise new approaches and interventions that can improve health, well-being, and quality of life. This edition of the Yearbook acknowledges the fact that we just started to explore the opportunities that ‘Big Data’ will bring. However, it will become apparent to the reader that its pervasive nature has invaded all aspects of biomedical informatics – some to a higher degree than others. It was our goal to provide a comprehensive view at the state of ‘Big Data’ today, explore its strengths and weaknesses, as well as its risks, discuss emerging trends, tools, and applications, and stimulate the development of the field through the aggregation of excellent survey papers and working group contributions to the topic.Conclusions: For the first time in history will the IMIA Yearbook be published in an open access online format allowing a broader readership especially in resource poor countries. For the first time, thanks to the online format, will the IMIA Yearbook be published twice in the year, with two different tracks of papers. We anticipate that the important role of the IMIA yearbook will further increase with these changes just in time for its 25th anniversary in 2016.
Keywords: Editorial; 2014 IMIA Yearbook of Medical Informatics; open access online format; Big Data; survey of biomedical informatics; IMIA and its societies